Performance of short and long range wireless communication technologies in construction - Rahnamayiezekavat, Payam; Moon, S.; Bernold, L. (Elsevier BV, 2014)
The ever increasing complexity of construction projects asks for improved communication and automated data collection supported by continually improving electronic tools. Advances in information technologies enable us to link critical resources on construction sites, such as trucks and cranes, to the project website creating many opportunities to drastically improve productivity, safety and quality. While the use of electronic equipment is nothing new in construction, no model exists to integrate them into one unified framework. This paper presents a wireless site-network concept consisting of information hubs enabled to automatically connect data sinks with sources supported by software agents. Included in this paper is the discussion of a mobile information hub, the eCKiosk, enabled to connect the work crew electronically to the project network while collecting automatically live “as-built” data. It begins with a review of long range wireless as the basis for designing a robust Agile Site Communication Network (ASCNet). Site experiments with short range wireless conduits and embedded RFID tags showed that they are able to provide information far beyond an identification number. While wireless technologies are poised to open totally new avenues to manage construction, more field-tests are needed to establish a solid knowledge base to create a pervasive network for the dynamically changing building site.